CHARACTERIZATION OF MICROSTRUCTURAL AND OPTICAL PROPERTIES OF MgFe2O4 NANOPARTICLES FOR PHOTOCATALYST OF MERCURY (Hg) - Rachmad Almi Putra; Rahmawati Rahmawati; Wan Alamsyah; I PT Indrayana (Jurnal Neutrino: Jurnal Fisika dan Aplikasinya)
The photodegradation activity of MgFe2O4 nanoparticles for Hg waste has been successfully performed. The MgFe2O4nanoparticles have been synthesized by the coprecipitation method. The obtained sample was characterized for their microstructural properties by using X-ray diffraction. The results confirmed that the sample was polycrystalline and has a spinel crystal structure with space group Fd3m.  The size of the crystallite is about 29.4 ± 0.2 nm. The gap energy of the sample was calculated from the UV-Vis results (4.17 eV). Furthermore, the MgFe2O4 nanoparticles can be used as functional photocatalyst material for degradation of mercury (Hg) ions in wastewater.